Effect of rifampicin on expression of lacZ fused to promoters or terminators of the E.coli rpoBC operon. - Howe, K M (1982)
The genes encoding the beta and beta' subunits of RNA polymerase in E.coli lie downstream of at least two ribosomal protein genes in a single unit of transcription. Treatment of E.coli with rifampicin, under conditions producing partial inhibition of general RNA synthesis, can strongly stimulate transcription of the polymerase genes, while activating the neighbouring ribosomal genes only slightly. We have investigated the mechanism of this effect by fusing strong promoters, a weak internal promoter, and an attenuator of the polymerase operon to the lacZ gene, in derivatives of plasmid pMC81. Studies of these fusions confirm our conclusion, based on similar fusions to galK, that rifampicin can foster readthrough of transcriptional terminators. They also suggest the existence of extra terminators and anti-termination elements in the above transcription unit.